A comparison of the clinical and antibacterial effects between tualang honey and manuka honey as adjunctive treatment in pseudomonas keratitis in rabbit eyes - Md Said , Haslinda (2017)
Honey is a known alternative therapy for varies diseases. Manuka honey antibacterial eye drop is established marketed honey for eye infection. We aim to explore the potential of Tualang honey to be commercialized in ophthalmic usage. Thus, we conducted an experimental study to compare the clinical and antibacterial effects of Tualang and Manuka honey as adjunctive treatment in Pseudomonas keratitis. Several in vitro studies documented that Tualang and Manuka honey had antibacterial effect towards Pseudomonas aeruginosa. This study is done to compare the mean Slit Lamp Examination (SLE) score and mean Colony Forming Unit (CFU) count of Pseudomonasinduced keratitis in rabbit eyes. This experimental animal study consisted of 20 rabbits induced with Pseudomonas keratitis that were randomly and equally divided into two groups. Group A was treated with a combination of Tualang honey 30% and gentamycin 0.3% eight times per day, while Group B was treated with a combination of Manuka honey and gentamycin 0.3% eight times per day. At the same time, a parallel study with similar methodology was conducted on ten rabbits which were treated with gentamycin 0.3% as a control group. Serial clinical examination using Slit Lamp Examination (SLE) score was done at 24, 48, 72 hours, Day 5 and Day 7. All rabbits were euthanized at Day 7 and their corneas harvested. The harvested corneas were processed and Colony Forming Unit (CFU) counts were performed on the next day. Repeated measure ANOVA and Mann-Whitney test were used for the data analysis. There was no statistically significant difference of clinical outcome (p=0.434) and antibacterial effect (p=0.198) between Tualang honey and Manuka honey as adjunctive treatment in Pseudomonas keratitis.Tualang honey is comparable to Manuka honey as adjunctive treatment in Pseudomonas keratitis in rabbit eyes.